2018
DOI: 10.1039/c8tc02381f
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the effective work function at buried organic/metal interfaces with organic solar cell characteristics

Abstract: Self-generated interlayers provide insight on the energy level alignment at the organic semiconductor/back contact interface in organic solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Work function is by definition a surface property and the EWF at interfaces depends on the electrochemical and electrical properties of the interfacing materials, and the chemical and physical interactions between them . Hence, work function values measured for bare metal surfaces or even distinctly prepared additive/metal interfaces do not necessarily reflect the energy level alignment at the organic/metal buried interface . Moreover, specific processing condition employed to fabricate the sample for direct energy level study may differ from those adopted for actual device fabrication .…”
Section: Resultsmentioning
confidence: 99%
“…Work function is by definition a surface property and the EWF at interfaces depends on the electrochemical and electrical properties of the interfacing materials, and the chemical and physical interactions between them . Hence, work function values measured for bare metal surfaces or even distinctly prepared additive/metal interfaces do not necessarily reflect the energy level alignment at the organic/metal buried interface . Moreover, specific processing condition employed to fabricate the sample for direct energy level study may differ from those adopted for actual device fabrication .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, OPVs with BIPO and TIPO interfacial materials exhibited drastic increases in all photovoltaic parameters, as expected. The higher V oc values of OPVs with interfacial layers, compared to those of OPVs with Al-only cathodes, are attributable to the increased work function differences between the anodes and cathodes. The work function of the cathode decreased on introduction of an interfacial layer; the difference between the effective work functions of the anode and cathode thus increased. The increased V oc values of OPVs with interfacial layers support the results of the UPS measurements discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we recently showed that interlayers composed of two molecules, one that effectively reduces the barrier for electron injection and the second that effectively reduces the barrier for hole injection, perfectly balance ambipolar OFET performance. 14,18,19 Deposition of such interlayers requires judicious materials selection and sensitive tuning and processing of the distinct interlayers, which inflict significant complications on device manufacturing and cost effectiveness. Therefore, it is necessary to develop a practical and simple solution for barrierless injection of both electrons and holes from one type of electrode into an organic semiconductor film.…”
Section: Introductionmentioning
confidence: 99%